Directors' Dealings am deutschen Kapitalmarkt - Büchs, Daniel; Ditter, Dominik; Henselmann, Klaus; Hering, Jörg; Götz, Michael (Zeitschrift für Corporate Governance, 2016)

Numerical study of droplet evaporation in an acoustic levitator - Bänsch, Eberhard; Götz, Michael (Physics of Fluids, 2018)
We present a finite element method for the simulation of all relevant processes of the evaporation of a liquid droplet suspended in an acoustic levitation device. The mathematical model and the numerical implementation take into account heat and mass transfer across the interface between the liquid and gaseous phase and the influence of acoustic streaming on this process, as well as the displacement and deformation of the droplet due to acoustic radiation pressure. We apply this numerical method to several theoretical and experimental examples and compare our results with the well-known d(2)-law for the evaporation of spherical droplets and with theoretical predictions for the acoustic streaming velocity. We study the influence of acoustic streaming on the distribution of water vapor and temperature in the levitation device, with special attention to the vapor distribution in the emerging toroidal vortices. We also compare the evaporation rate of a droplet with and without acoustic streaming, as well as the evaporation rates in dependence of different temperatures and sound pressure levels. Finally, a simple model of protein inactivation due to heat damage is considered and studied for different evaporation settings and their respective influence on protein damage. Published by AIP Publishing.